A polymer electrolyte and preparation method thereof and lithium-ion all-solid-state battery

By crosslinking polyvinylpyrrolidone with polyethylene oxide and filling the precursor solution, the problems of lithium ion migration difficulties and large interface impedance caused by high crystallinity of polymer electrolytes are solved, and high ionic conductivity and excellent cycling performance are achieved.

CN115224359BActive Publication Date: 2025-04-04SHAANXI COAL & CHEM TECH INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210885723.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-26
Publication Date
2025-04-04
Estimated Expiration
2042-07-26

AI Technical Summary

Technical Problem

The high crystallinity of polymer electrolytes in lithium batteries leads to difficulty in transfer of lithium ions, low ion conductivity, and the interface impedance between the positive and negative electrodes of all-solid-state batteries and the electrolyte membrane is large, resulting in poor circulation performance.

Method used

By crosslinking with polyethylene oxide with polyethylene oxide, the crystallinity of the polyethylene oxide polymer electrolyte is reduced, and the precursor solution of vinyl carbonate and lithium di(trifluoromethylsulfonyl)imide is filled in the polymer electrolyte membrane with a porous network structure to achieve gradient distribution of the electrolyte.

Benefits of technology

The ionic conductivity of polymer electrolyte is improved, the interface impedance between the positive and negative electrodes and the electrolyte membrane is reduced, and the circulation and capacity performance of all-solid-state batteries are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003765572170000011
    Figure HDA0003765572170000011
  • Figure HDA0003765572170000012
    Figure HDA0003765572170000012
  • Figure HDA0003765572170000013
    Figure HDA0003765572170000013
Patent Text Reader

Abstract

The present invention provides a polymer electrolyte and a preparation method thereof and a lithium ion all-solid-state battery, wherein the polymer electrolyte comprises a continuous phase and a dispersed phase, wherein the raw materials for preparing the continuous phase comprise polyvinyl pyrrolidone, polyethylene oxide and lithium bis(trifluoromethylsulfonyl)imide, and the raw materials for preparing the dispersed phase comprise vinylene carbonate, lithium bis(trifluoromethylsulfonyl)imide and an initiator. The present invention improves the ionic conductivity of the polymer electrolyte, and at the same time achieves full contact between the polymer electrolyte and the electrode active material, effectively solves the interface problem between the polymer electrolyte membrane and the positive and negative electrode sheets, and effectively improves the cycle performance of the all-solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a polymer electrolyte and a preparation method thereof, and a lithium ion all-solid-state battery. Background Art

[0002] Compared with liquid electrolyte systems, polymer electrolytes have many advantages, such as no leakage, easy miniaturization of devices, and higher safety. As early as the 1920s, scholars discovered that inorganic solid electrolytes, such as AgI crystals, have superionic conductivity at temperatures above the phase transition temperature of the β phase and the a phase (149°C), which first made the concept of "polymer electrolyte" a reality in 1920; after that, superionic conductors with similar crystal states were continuously developed, and the room temperature ionic conductivity reached 10 -3 ~10 -4 S / cm level. However, the preparation of inorganic solid electrolytes and the poor contact of their interfaces are their major shortcomings; in contrast, polymer materials have many excellent properties, such as good ductility, light weight, and easy mechanical processing. The excellent properties of polymer materials have led to the rapid development of polymer electrolytes in the field of lithium batteries.

[0003] Polymer electrolytes usually have excellent mechanical properties, which can effectively inhibit the growth of lithium dendrites in the lithium metal negative electrode during the charge and discharge process, thus improving the safety performance of lithium batteries. At present, the most studied polymer electrolyte is the polyethylene oxide (PEO) system, but its high crystallinity makes it difficult for lithium ions to migrate at room temperature, resulting in low ion conductivity.

[0004] Moreover, after assembling the all-solid-state battery, the interface impedance between the positive and negative electrodes and the electrolyte membrane is large, resulting in poor capacity utilization and poor cycle performance of the all-solid-state battery. Summary of the invention

[0005] The purpose of the present invention is to develop a polymer electrolyte and a preparation method and a lithium-ion all-solid-state battery, so as to improve the ionic conductivity of the polymer electrolyte, while achieving full contact between the polymer electrolyte and the electrode active material, effectively solving the interface problem between the polymer electrolyte membrane and the positive and negative electrode sheets, and effectively improving the cycle performance of the all-solid-state battery.

[0006] The present invention is achieved through the following technical solutions:

[0007] The present invention provides a method for preparing a polymer electrolyte, the preparation steps comprising:

[0008] S1. Preparation of polymer electrolyte membrane: Weigh a certain amount of polyvinyl pyrrolidone (PVP), polyethylene oxide (PEO) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) respectively and dissolve them in a good solvent to prepare a uniform solution to obtain a polymer electrolyte slurry. The electrolyte slurry is poured on a PTFE plate to form a film, and then immersed in an ethanol solution for defoaming to finally obtain a polymer electrolyte membrane with a porous structure.

[0009] S2. Preparation of precursor solution: vinylene carbonate and lithium bis(trifluoromethylsulfonyl)imide are mixed evenly in a certain proportion to form a uniform solution, an initiator is added, and the mixture is slowly stirred to form a precursor solution.

[0010] S3. Preparation of in-situ polymer electrolyte: Use a rubber-tipped dropper to drip a certain amount of S2 precursor solution (selected according to the size and pore size of the membrane) into the polymer electrolyte membrane prepared in S1, so that it fills the entire porous structure. Then place it in a vacuum oven for in-situ polymerization and peeling to obtain a polymer electrolyte.

[0011] Preferably, in S1, the mass ratio of polyvinyl pyrrolidone, polyethylene oxide and lithium bis(trifluoromethylsulfonyl)imide is (0.2-0.6):(2-3.2):(0.6-0.8).

[0012] Preferably, in S1, the good solvent is one of acetone, N,N-dimethylformamide and acetonitrile. Preferably, the good solvent is acetonitrile.

[0013] Preferably, in S1, the soaking time in ethanol is 1 min to 20 min, and preferably, the soaking time in S1 is 5 min.

[0014] Preferably, in S2, the molar ratio of vinylene carbonate to lithium bis(trifluoromethylsulfonyl)imide is (2-4):1, preferably, the molar ratio of vinylene carbonate to lithium bis(trifluoromethylsulfonyl)imide in S2 is 3:1.

[0015] Preferably, in S2, the initiator is one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate. Preferably, the initiator in S2 is azobisisobutyronitrile.

[0016] Preferably, in S3, the in-situ polymerization temperature is 45°C to 90°C, and the polymerization time is 1h to 3h. Preferably, the polymerization temperature in S3 is 60°C, and the polymerization time is 2h.

[0017] The present invention also provides a polymer electrolyte, which includes a polymer electrolyte membrane with a porous network structure and a dispersed phase filled in the porous network structure of the polymer electrolyte membrane; the polymer electrolyte membrane includes a polyethylene oxide matrix, in which polyvinyl pyrrolidone and lithium bis(trifluoromethylsulfonyl)imide are cross-linked; the dispersed phase is a polymer of vinylene carbonate and lithium bis(trifluoromethylsulfonyl)imide.

[0018] Preferably, in the polymer electrolyte membrane, the mass ratio of polyvinyl pyrrolidone, polyethylene oxide and lithium bis(trifluoromethylsulfonyl)imide is (0.2-0.6):(2-3.2):(0.6-0.8).

[0019] Preferably, in the dispersed phase, the molar ratio of vinylene carbonate to lithium bis(trifluoromethylsulfonyl)imide is (2-4):1.

[0020] The present invention also provides a lithium-ion all-solid-state battery, comprising a positive electrode, a negative electrode and the above-mentioned polymer electrolyte located between the positive electrode and the negative electrode.

[0021] Preferably, the positive electrode is obtained by coating a positive electrode slurry on a current collector, and the raw materials for preparing the positive electrode slurry include: vinylene carbonate, lithium bis(trifluoromethylsulfonyl)imide, an initiator and a positive electrode active substance; the negative electrode is obtained by coating a negative electrode slurry on a current collector, and the raw materials for preparing the negative electrode slurry include: vinylene carbonate, lithium bis(trifluoromethylsulfonyl)imide, an initiator and a negative electrode active substance.

[0022] The present invention also provides a method for preparing a lithium-ion all-solid-state battery: using the precursor solution in S2 as a solvent, adding a positive electrode active material to prepare a positive electrode slurry, and then coating it on a current collector to form a positive electrode; using the precursor solution in S2 as a solvent, adding a negative electrode active material to prepare a negative electrode slurry, and then coating it on a current collector to form a negative electrode, the positive electrode and the negative electrode are assembled into a lithium battery with the in-situ polymer electrolyte in S3, and after packaging, they are in-situ cured to obtain an all-solid-state battery.

[0023] Preferably, the curing conditions are a curing temperature of 45°C to 90°C and a curing time of 1h to 3h. Preferably, the curing temperature is 60°C and the curing time is 2h.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The polymer electrolyte preparation method of the present invention effectively reduces the problem of high crystallinity of polyethylene oxide polymer electrolyte by cross-linking polyvinyl pyrrolidone with polyethylene oxide, thereby improving the ionic conductivity of the polymer electrolyte and overcoming the shortcomings of the PEO system. At the same time, the present invention fills the precursor solution of the electrolyte in the polymer electrolyte membrane with a porous network structure, and the electrolyte retained in the porous network structure penetrates into the interface and surface of the positive and negative electrodes during the manufacture of the battery, so that the electrolyte is distributed in a gradient throughout the battery, effectively reducing the interface impedance and improving the ion mobility.

[0026] Furthermore, the present invention optimizes the solvent, and other polar solvents cannot prepare the desired porous structure electrolyte.

[0027] The polymer electrolyte of the present invention can reduce the crystallinity of the polyethylene oxide polymer electrolyte by cross-linking polyvinyl pyrrolidone with polyethylene oxide, thereby improving the ionic conductivity of the polymer electrolyte, and the maximum room temperature ionic conductivity is greater than 10 -4 S / cm, with high ionic conductivity, overcoming the shortcomings of the PEO system. At the same time, the present invention fills (trifluoromethylsulfonyl) imide lithium in the polymer electrolyte membrane, which penetrates into the interface and surface of the positive and negative electrodes during the manufacture of the battery, so that the electrolyte is distributed in a gradient throughout the battery, effectively reducing the interface impedance and improving the ion mobility. At the same time, the polymer electrolyte improves the mechanical strength, broadens the electrochemical window, has good corrosion resistance, is not easily soluble in organic solvents, and can also be applied to lithium batteries with solid-liquid mixed electrolytes.

[0028] The lithium-ion all-solid-state battery of the present invention adopts the polymer electrolyte of the present invention. The electrolyte filled in the polymer electrolyte penetrates into the positive and negative electrodes, so that the slurry with lithium ion conductivity is gradiently distributed in the entire solid-state battery, constructing an integrated structure, effectively solving the interface problem between the polymer electrolyte membrane and the positive and negative electrode sheets, and effectively improving the cycle performance and capacity performance of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a macroscopic picture of a polymer electrolyte membrane with a porous network structure;

[0030] Figure 2 This is a picture of the corrosion resistance of the polymer electrolyte membrane;

[0031] Figure 3 It is the discharge curve diagram of the all-solid-state battery;

[0032] Figure 4 This is the cycle curve of the all-solid-state battery. DETAILED DESCRIPTION

[0033] In order to further understand the present invention, the present invention is described below in conjunction with embodiments. These descriptions are only to further explain the features and advantages of the present invention and are not intended to limit the claims of the present invention.

[0034] Example 1: Preparation method and application of a polymer electrolyte:

[0035] Step 1, preparation of porous electrolyte membrane: PVP 0.45g, PEO 2.26g, LiTFSI 0.74g were weighed and dissolved in acetonitrile solvent, the amount of acetonitrile was 13.8g, and stirred at 500rpm / min for 4h to form a uniform solution to obtain polymer electrolyte slurry. The electrolyte slurry was cast on a PTFE plate to form a film, and then soaked in ethanol for 5min to defoam, and finally a polymer electrolyte membrane with a porous structure was obtained, such as Figure 1 shown.

[0036] Step 2, preparation of a precursor solution: weigh 22.63 g of vinylene carbonate and put it into a reactor, then weigh 7.37 g of lithium salt LiTFSI and add it into the reactor, after LiTFSI is completely dissolved in vinylene carbonate, weigh 0.02 g of azobisisobutyronitrile and add it into the reactor, slowly stir until it is completely dissolved to form a uniform solution, and obtain a precursor solution.

[0037] Step 3, preparation of in-situ polymer electrolyte: 10 mL of precursor solution was added to the polymer electrolyte membrane using a rubber-tipped dropper to fill the entire porous electrolyte membrane. The membrane was then placed in a vacuum oven at 60° C. for polymerization for 2 h to obtain an in-situ polymer electrolyte.

[0038] Step 4: Use the precursor solution prepared in step 2 as a solvent to prepare lithium iron phosphate positive electrode and graphite negative electrode slurry, then apply it on the current collector, and assemble the lithium battery with the in-situ polymer electrolyte prepared in step 3 filled with the precursor solution. After packaging, in-situ cure at 60°C for 2h to obtain an all-solid-state battery 1, and then start testing after maintaining the temperature for 22h.

[0039] Example 2

[0040] Step 1, preparation of porous electrolyte membrane: weigh 0.6g of PVP, 3.2g of PEO, and 0.8g of LiTFSI respectively and dissolve them in acetonitrile solvent, the amount of acetonitrile is 13.8g, stir at 500rpm / min for 4h to form a uniform solution, and obtain polymer electrolyte slurry. The electrolyte slurry is cast on a PTFE plate to form a film, and then soaked in ethanol for 5min to defoam, and finally a polymer electrolyte membrane with a porous structure is obtained, such as Figure 1 shown.

[0041] Step 2, preparation of a precursor solution: weigh 22.63 g of vinylene carbonate and put it into a reactor, then weigh 7.37 g of lithium salt LiTFSI and add it into the reactor, after LiTFSI is completely dissolved in vinylene carbonate, weigh 0.02 g of azobisisobutyronitrile and add it into the reactor, slowly stir until it is completely dissolved to form a uniform solution, and obtain a precursor solution.

[0042] Step 3, preparation of in-situ polymer electrolyte: 10 mL of precursor solution was added to the polymer electrolyte membrane using a rubber-tipped dropper to fill the entire porous electrolyte membrane. The membrane was then placed in a vacuum oven at 45° C. for polymerization for 3 h to obtain an in-situ polymer electrolyte.

[0043] Step 4: Use the precursor solution prepared in step 2 as a solvent to prepare lithium iron phosphate positive electrode and graphite negative electrode slurry, then apply it on the current collector, and assemble the lithium battery with the in-situ polymer electrolyte prepared in step 3 filled with the precursor solution. After packaging, in-situ cure at 45°C for 3h to obtain an all-solid-state battery 2, and then start testing after maintaining the temperature for 22h.

[0044] Example 3

[0045] Step 1, preparation of porous electrolyte membrane: PVP 0.2g, PEO 2.0g, LiTFSI 0.6g were weighed and dissolved in acetonitrile solvent, the amount of acetonitrile was 13.8g, and stirred at 500rpm / min for 4h to form a uniform solution to obtain polymer electrolyte slurry. The electrolyte slurry was cast on a PTFE plate to form a film, and then soaked in ethanol for 5min to defoam, and finally a polymer electrolyte membrane with a porous structure was obtained, such as Figure 1 shown.

[0046] Step 2, preparation of a precursor solution: weigh 22.63 g of vinylene carbonate and put it into a reactor, then weigh 7.37 g of lithium salt LiTFSI and add it into the reactor, after LiTFSI is completely dissolved in vinylene carbonate, weigh 0.02 g of azobisisobutyronitrile and add it into the reactor, slowly stir until it is completely dissolved to form a uniform solution, and obtain a precursor solution.

[0047] Step 3, preparation of in-situ polymer electrolyte: 10 mL of precursor solution was added to the polymer electrolyte membrane using a rubber-tipped dropper to fill the entire porous electrolyte membrane. The membrane was then placed in a vacuum oven at 90° C. for polymerization for 1 h to obtain an in-situ polymer electrolyte.

[0048] Step 4: Use the precursor solution prepared in step 2 as a solvent to prepare lithium iron phosphate positive electrode and graphite negative electrode slurry, then apply it on the current collector, and assemble the lithium battery with the in-situ polymer electrolyte prepared in step 3 filled with the precursor solution. After packaging, in-situ cure at 90°C for 1h to obtain an all-solid-state battery 3, and then start testing after maintaining the temperature for 22h.

[0049] Comparative Example 1

[0050] Step 1. Weigh 2.3g of polymer PEO and 0.7g of lithium salt LiTFSI, slowly add them into the solvent acetonitrile, the amount of acetonitrile is 13.8g, and magnetically stir for 5h at a speed of 500rpm / min to obtain a polymer electrolyte slurry. Pour the prepared slurry on a PTFE mold and place it in a drying room to dry to prepare a non-porous polymer electrolyte. Assemble a button battery in the order of negative electrode shell, gasket, polymer electrolyte, gasket, shrapnel, and positive electrode shell, and test its ionic conductivity at 25℃, 45℃, 65℃, and 85℃.

[0051] Step 2: Assemble the prepared polymer electrolyte with LFP (LiFePO4) and metal lithium negative electrode to assemble the all-solid-state battery 2, and test its electrochemical performance. At 60°C, 3.65V~2.5V, 0.2C charge and discharge, the all-solid-state battery 2 cannot be charged and discharged normally, which may be caused by the poor physical contact between the positive and negative electrodes and the polymer electrolyte membrane, resulting in a large internal resistance.

[0052] The polymer electrolyte membrane of Example 1 was subjected to a corrosion test, and the corrosion solution was an electrolyte solution composed of 1M lithium hexafluorophosphate and dimethyl carbonate / ethylene carbonate / ethyl methyl carbonate (mass ratio 1:1:1), such as Figure 2 As shown, it can be seen that the traditional electrolyte membrane material has been dissolved in the organic electrolyte, and the porous polymer electrolyte prepared by the present invention will not be corroded and dissolved in the organic electrolyte, has good corrosion resistance, and can be matched with liquid electrolytes to prepare solid-liquid mixed lithium batteries.

[0053] The ionic conductivity of the polymer electrolytes obtained in Examples 1-3 and Comparative Example 1 was tested, and the results are shown in Table 1. It can be seen that the ionic conductivity of the polymer electrolytes of Examples 1-3 in the electrical performance test is significantly higher than that of the polymer electrolyte of Comparative Example 1, indicating that the addition of PVP can improve the ionic conductivity of the polymer electrolyte.

[0054] Table 1 Absolute values ​​of ionic conductivity of polymer electrolyte membranes

[0055] Comparative Example 1 Example 1 Example 2 Example 3 25℃ 4.16E-06 1.05E-04 8.16E-06 5.23E-06 45℃ 4.53E-05 6.15E-04 6.3E-05 4.83E-05 65℃ 3.58E-04 2.66E-03 5.85E-04 3.94E-04 85℃ 8.05E-04 6.37E-03 9.1E-04 9.17E-04

[0056] The all-solid-state battery 1 and the all-solid-state battery 2 prepared in Example 1 and Comparative Example 1 were subjected to electrical performance tests to test their cycle performance and charge-discharge performance. Figure 3 The discharge curves of the solid-state batteries of Comparative Example 1 and Example 1 are shown in FIG. Figure 3It can be seen that the all-solid-state battery prepared in Example 1 has a discharge energy of 152 mAh / g at a discharge current of 0.2C, has a discharge platform of 3.4V, and a standard charge and discharge curve of lithium iron phosphate material. Compared with the solid-state battery of Comparative Example 1, the all-solid-state battery of Example 1 has a discharge capacity 30 mAh / g higher, has good discharge capability, and is close to the theoretical discharge energy of lithium iron phosphate material. Figure 4 The cycle performance diagram of the solid-state battery of Comparative Example 1 and Example 1 is shown in FIG. Figure 4 It can be seen that the capacity retention rate of the solid-state battery of Example 1 after 0.2C cycle 30 cycles reaches 99.8%, and the capacity retention rate of the solid-state battery of Comparative Example 1 after 0.2C cycle 30 cycles is less than 40%, which fully demonstrates that the solid-state battery prepared in Example 1 has reversible lithium insertion and extraction capabilities and excellent cycle performance.

[0057] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium-ion all-solid-state battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a polymer electrolyte located between the positive electrode and the negative electrode; the polymer electrolyte comprises a polymer electrolyte membrane having a porous network structure and a dispersed phase filled in the porous network structure of the polymer electrolyte membrane; the polymer electrolyte membrane comprises a polyethylene oxide matrix, in which polyvinyl pyrrolidone and lithium bis(trifluoromethylsulfonyl)imide are cross-linked; the dispersed phase is a polymer of vinylene carbonate and lithium bis(trifluoromethylsulfonyl)imide; the positive electrode is obtained by coating a positive electrode slurry on a current collector and curing it, the positive electrode slurry comprises: vinylene carbonate, lithium bis(trifluoromethylsulfonyl)imide, an initiator and a positive electrode active material; the negative electrode is obtained by coating a negative electrode slurry on a current collector and curing it, the negative electrode slurry comprises: vinylene carbonate, lithium bis(trifluoromethylsulfonyl)imide, an initiator and a negative electrode active material.

2. The lithium-ion all-solid-state battery according to claim 1, characterized in that: In the polymer electrolyte membrane, the mass ratio of polyvinyl pyrrolidone, polyethylene oxide and lithium bis(trifluoromethylsulfonyl)imide is (0.2~0.6):(2~3.2):(0.6~0.8).

3. The lithium-ion all-solid-state battery according to claim 1, characterized in that: In the dispersed phase, the molar ratio of vinylene carbonate to lithium bis(trifluoromethylsulfonyl)imide is (2~4):

1.

4. The lithium-ion all-solid-state battery according to claim 1, characterized in that: The method for preparing the polymer electrolyte comprises: S1, dissolving polyvinyl pyrrolidone, polyethylene oxide and lithium bis(trifluoromethylsulfonyl)imide in a good solvent to obtain an electrolyte slurry, and casting the electrolyte slurry on a substrate to form a film to obtain a polymer electrolyte membrane with a porous structure; S2, mixing vinylene carbonate, lithium bis(trifluoromethylsulfonyl)imide and an initiator to obtain a precursor solution; S3, dripping a precursor solution onto the polymer electrolyte membrane, allowing the precursor solution to fill the pores in the polymer electrolyte membrane and polymerize in situ, and then peeling the polymer electrolyte membrane from the substrate to obtain a polymer electrolyte.

5. The lithium-ion all-solid-state battery according to claim 4, characterized in that: In S1, the good solvent is one of acetone, N,N-dimethylformamide and acetonitrile.

6. The lithium-ion all-solid-state battery according to claim 4, characterized in that: In S2, the initiator is one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.

7. The lithium-ion all-solid-state battery according to claim 4, characterized in that: In S3, the temperature of the in-situ polymerization is 45°C to 90°C, and the time is 1h to 3h.

Citation Information

Patent Citations

  • Vinylene carbonate-based lithium ion battery polymer electrolyte and preparation method as well as application thereof

    CN105826603A